Semiconductor photocatalysts: A critical review highlighting the various strategies to boost the photocatalytic performances for diverse applications - Ahmad, Irshad; Zou, Yanhong; Yan, Jiaying; Liu, Yuyu; Shukrullah, Shazia; Naz, Muhammad Yasin; Hussain, Humaira; Khan, Waheed Qamar; Khalid, N.R. (Advances in colloid and interface science, 2023)
The photocatalytic technology illustrates an eco-friendly and sustainable route to overcome environmental and energy issues. The successful construction of a photocatalyst depends on four key elements: light absorption ability, the density of active sites, redox capacity, and photoinduced electron-hole recombination rate. Sincemost of intrinsic semiconductor photocatalysts cannot meet all these requirements, they are often modified to boost their photocatalytic properties. Many strategies have been adopted to design novel and efficient photocatalysts for diverse applications. Herein, we review the most efficient of these strategies and methods focused on effectively overcoming the efficiency limitations of photocatalysts to promote their large-scale application. Subsequently, a particular aim is put on the most current studies for photocatalytic applications, including CO2 reduction, N2 fixation, H2 evolution, and pollutants degradation. Finally, key challenges and future perspectives in designing and implementing semiconductor photocatalysts for large-scale applications are discussed. Therefore, it is foreseen that this review will work as a guide for future research and provides a variety of strategies to develop novel and high-performance photocatalysts for various applications. [Display omitted] •Recent advances in strategies to design semiconductor catalysts are discussed.•The mechanism of various strategies for photocatalytic performance are highlighted.•The effect of diverse strategies on the photocatalytic performance is summarized.•Combination of different strategies leads to further increased performance.•Challenges pertaining the use of semiconductor catalysts are reviewed.